2017
DOI: 10.1007/s11664-017-5999-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact Factors Analysis of the Hot Side Temperature of Thermoelectric Module

Abstract: The thermoelectric generator (TEG) plays a crucial role in converting the waste energy of exhaust into electricity, which ensures energy saving and increased fuel utilization efficiency. In the urban driving cycle, frequent vehicle operation, like deceleration or acceleration, results in continuous variation of the exhaust temperature. In order to make the operating performance stable, and to weaken the adverse effects of the frequent variation of the exhaust temperature on the lifetime and work efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Chen et al have shown that fluctuating temperature boundary conditions have adverse effects on TEG output performance [12,13]. Zhang et al found that fluctuating conditions of the hot side of the TE module will lead to instability and low efficiency of the TEG system [14]. Jia et al analyzed the response under an exponential transient heat source.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al have shown that fluctuating temperature boundary conditions have adverse effects on TEG output performance [12,13]. Zhang et al found that fluctuating conditions of the hot side of the TE module will lead to instability and low efficiency of the TEG system [14]. Jia et al analyzed the response under an exponential transient heat source.…”
Section: Introductionmentioning
confidence: 99%